Underdevelopment of sport in Nigeria: A need for physical education curriculum diversification (2010)
This paper focuses on the need for physical education curriculum diversification in order to achieve sustainable sport development in Nigeria. It compares level of sport development in Nigeria with other countries with the aim of bringing to limelight the reason why there is disparity. The paper also considered need for physical education curriculum diversification having compare physical education curriculum across many countries. It was concluded in the paper that education is a dynamic phenomenon that must recognize the changes in the environment and respond to the growing demands and challenges. Physical education is a large system and it is almost impossible to predict its behaviour over far too distant future since the system parameters show a high rate of change. In today's scenario, the sport business is changing so rapidly that other sport disciplines are fast appearing on the surface. Mobility of sport professionals across the national boundaries has changed the demand - supply perspective and this may eventually force the educational planners to take a global view. Physical education programs in Nigerian higher institutions are based in the school of education. This practice has dwarfed the scope of these programs and has made them unpopular. Because Nigerian teachers are so poorly paid, most young people do not choose teaching as a profession. Physical education programs, particularly teachers of physical education and recreation, sport coaches, administrators, technologists, journalists, trainers and consultants must receive proper training. An urgent need exists to develop programs outside the colleges of education that meet the needs of physical education students who do not want to become teachers